Gephyrocharax machadoi, a new species of Stevardiinae (Characiformes: Characidae) from the Rio Paraguai basin, central Brazil - Ferreira, Katiane M.; De Faria, Erika; Ribeiro, Alexandre C.; Santana, Julio C. O.; Quagio-Grassioto, Irani [UNESP]; Menezes, Naercio A. (Magnolia Press, 2018)
Gephyrocharax machadoi, new species, is described from tributaries of the rio Sepotuba, upper rio Paraguai basin, Mato Grosso state, Brazil. The new species is distinguished from its congeners, except Gephyrocharax major, by presenting two modified scales on the ventral caudal-fin lobe (pouch scales): a larger, sexually dimorphic scale, slightly superior and anterior in position, followed by a smaller, posterior and ventrally placed accessory scale (vs. a single modified pouch scale without ventrally placed accessory scales). Gephyrocharax machadoi differs from G. major by presenting a gap (more conspicuous in mature males than in mature females) between the second and third ventral procurrent caudal-fin rays (vs. second and third ventral procurrent caudal-fin rays near each other or fused distally); premaxilla with tricuspid teeth (vs. tetra-to pentacuspid teeth); and body depth 21.5-25.4% of SL (vs. 25.9-36.8% in SL). Spermiogenesis and spermatozoa morphology are also described.
Keywords: Stevardiini; Gephyrochrax major; pouch scale; rio Sepotuba; spermatozoa morphology